The self-complexity and its relationship with the shopaholics for girl arrears in marriage - Laeaby Shriji, Ebtisam (Al-Adab Journal, 2019)
The goals of the research are:- 1- Measuring the self- complexity for girl arrears in marriage.2- Measuring the shopaholism for girl arrears in marriage3- Identifying the relation between the self-complexity the shopaholism for girl arrears in marriage The research is applied on the girl arrears in marriage The sample included (200) girls. This research adopted a scale (Am -Maaen,2013) to measure the self-complexity. measure indicators for validity and reliability as was (0,73) and retesting (0,68) . The anther methods was for the shopaholism measure indicators for validity and reliability as was (0,75) and retesting (0,66) . The results showed the following :There is a low self-complexity for girl arrears in marriage.There is a the shopaholism for girl arrears in marriage in 22% .There is a negative relationship between self-complexity , and the shopaholism.